BENGKEL MODIFIKASI CUSTOM DI KOTA BANJARMASIN - Setiawan, Eko; Heldiansyah, J.C (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
The development in the automotive world is increasing every year, automotive manufacturers, especially motorcycles, compete to make and issue types and brands with the latest technology innovations. This encourages modification lovers to create and create modifications. South Kalimantan has considerable potential in the automotive field, especially custom modification workshops, the problem is the lack of complete workshops and facilities in one workshop, especially in the city of Banjarmasin. Custom modification workshop in Banjarmasin is very small in number, in addition it also has many shortcomings in terms of facilities and building characteristics. To answer these problems a custom modification workshop design is needed that has complete facilities in one place and has the characteristics of a modification workshop building in order to provide comfort and convenience for its visitors. The problem solving method applied is the Metaphor Architecture method, which later the metaphorical elements will be implemented in the form and space of the building. The design concept applies the concept of a custom identity motorcycle where the results of the custom modification workshop design consist of several characteristics and characteristics of a custom motorbike.